Moisturizing treatment of patients with atopic dermatitis and ichthyosis vulgaris improves dry skin, but has a modest effect on gene expression regardless of FLG genotype. (12th December 2013) - Hoppe, T.; Winge, M.C.G.; Bradley, M.; Nordenskjöld, M.; Vahlquist, A.; Törmä, H.; Berne, B.
Abstract Background Loss‐of‐function mutations in FLG (encoding filaggrin) are a predisposing factor for atopic dermatitis (AD) and cause ichthyosis vulgaris (IV). Patients with AD and IV display impaired skin barrier and dry skin, and altered epidermal expression of genes in pro‐inflammatory and lipid metabolic pathways are often evident. Objectives To evaluate the effect of three different moisturizers on skin barrier function and epidermal gene expression in patients with AD/IV in relation to FLG mutation status. Methods Patients (n = 43) were classified according to their FLG status: AD with FLG+/+ (n = 14), AD with FLG+/− (n = 14), and AD/IV with FLG−/− (n = 15). Dryness score and transepidermal water loss (TEWL) were monitored on volar forearms, and punch biopsies were taken for analysis of gene expression. Measurements were repeated after 4 weeks of treatment with either of two moisturizers on each forearm. Results Treatment with any of the three moisturizers significantly reduced dryness score and TEWL in the group as a whole. FLG−/− patients displayed the largest reduction in dryness score. Only minute changes occurred in the mRNA expression of 15 selected epidermal genes. Conclusions Moisturizing treatment improves dry skin and certain aspects of abnormal skin barrier function, especially in patients with AD/IV and dual FLG mutations, but does not normalize the epidermal gene expression profile.